Potential Molecular Mechanisms of 5-Aminolevulinic Acid Related to Acute Hepatic Porphyria via Transcriptome Profile Analysis - Talal Bin Quayyid Alotaibi , Ali Mosa Ahmad Khobrani , Sultan Mohammed Saegh , Abdulaziz Khater Jaber Alzahrani , Salman Mohammed Awthah Alshehri , Fawaz Ali Rashed Ghamdi , Ahmed Jamaan Ahmed Alghamdi; Hayat Abdulmalik Maqbool Althobaiti , Ziyad Mohammed Suwaylih Almuylibi , Jabbar Fettes Jabbar alghamdi , Saleh Matar Saleh Alzahrani (Migration Letters, 2022)
Acute hepatic porphyrias (AHPs) are inherited metabolic diseases that cause decreased activity or synthesis of heme biosynthesis pathway enzymes, resulting in elevated levels of 5-aminolevulinic acid (5-ALA) or porphobilinogen (PBG) in urine, stool, plasma, and organs such as the liver and brain. Our review looks at the effects of 5-aminolevulinic acid (5-ALA) on the livers of people with acute intermittent porphyria (AIP), a hereditary metabolic condition. The study discovered that 5-ALA, an α-aminoketone, can cause apoptosis, DNA damage, mitochondrial malfunction, & altered expression of carcinogen-related proteins. The researchers employed DNA microarrays to investigate the transcriptional alterations and molecular pathways in HepG2 cells after being exposed to 5-ALA for 2 and 24 hours. The findings revealed that 5-ALA ’25 mM-2h’ increased 10 genes related to oxidative stress response & carcinogenesis. The study also discovered that 5-ALA ’25 mM-24h’ enhanced pathways implicated in drug detoxification, oxidative stress, DNA damage, cell death/survival, cell cycle, and mitochondrial malfunction. The findings might help to enhance the efficacy of current medicines & lead to the creation of new biomarkers and targets for AHP/AIP diagnosis, prognosis, as well as therapy methods.